Report of the Working Group on the Development of the Capital Market - Planning Commission (Planning Commission, Government of India, 1989)
The Government of India Planning Commission Report (January 1989) on the Development of the Capital Market presents a comprehensive reform agenda aimed at strengthening financial intermediation, enhancing resource mobilization, and supporting sustained economic growth through a more efficient and inclusive capital market framework. Recognizing that inadequate capital accumulation and inefficient allocation have constrained India’s industrialization, the report underscores the need to shift from a debt-dominated financing culture toward greater reliance on equity financing, supported by stronger investor confidence and improved corporate transparency. It highlights structural deficiencies in the existing capital market, including speculative diversion of savings, limited participation beyond metropolitan centers, and insufficient support for new and small enterprises. The report recommends a multi-tiered listing system to facilitate access for firms of varying sizes, expansion of professionally managed mutual funds to democratize investment, and development of a robust venture capital ecosystem to support innovation and small and medium enterprises. It further advocates a rationalized interest rate structure linked to benchmark prime lending rates, reduction of administered rates, reform of priority sector lending, and greater flexibility for banks and financial institutions in pricing credit. Emphasis is placed on strengthening regulatory frameworks, enhancing disclosure norms, ensuring merchant banker accountability, and implementing tax reforms to eliminate double taxation and incentivize equity participation. Public financial institutions are encouraged to assume a promotional role aligned with national development priorities, while public enterprises are permitted controlled access to equity markets. Collectively, the report envisions a transparent, diversified, and resilient capital market system that broadens investor participation, supports entrepreneurship, and lays a durable foundation for accelerated and balanced economic development in India.
Government of India Planning Commission January, 1989
Keywords: Capital Market Development; Planning Commission Report 1989; Financial Intermediation; Equity Financing; Interest Rate Rationalization; Public Financial Institutions; Investor Protection Framework; Multi-Tier Listing System; Mutual Funds Expansion; Venture Capital Promotion; Tax Reforms for Investment; Priority Sector Lending Reform